Moisture dependent physical and mechanical properties of chickpea seeds - Amer Eissa, Ayman Hafiz; M A, Mohamed; H, Moustafa; Alghannam, Abdul Rahman O (International Journal of Agricultural and Biological Engineering, 2010)
Abstract: The moisture-dependent physical properties are important in designing and fabricating equipment and structures for handling, transporting, processing and storage, and also for assessing quality. This study was carried out to determine the effect of moisture content on some physical and mechanical properties for two varieties of chickpea seeds (Giza 3, and Giza 195). Four levels of moisture content ranging from 11.6% d.b. (dry basis) to 25.4% d.b. were used. The average length, width, thickness, and geometric mean diameter ranged from (7.92±0.04) mm to (8.14±0.04) mm, (6.10±0.04) mm to (6.37± 0.04) mm, (6.43±0.04) mm to (6.84±0.04) mm and (6.77±0.07) mm to (7.08±0.07) mm, respectively. The average sphericity and roundness ranged from (85.53±0.19)% to (87.00±0.19)% and (93.70±0.35)% to (94.14±0.35)%, respectively. The average measured surface area, calculated surface area, and projected area ranged from (144.73±1.55) mm2 to (158.78±1.55) mm2, (146.89±1.58) mm2 to (159.78±1.58) mm2, and (46.53±0.50) mm2 to (48.93±0.50) mm2, respectively. The average bulk density, true density, porosity and angle of repose ranged from (730.05±11.84) kg/m3 to (694.17±11.84) kg/m3, (1,225.12± 19.51) kg/m3 to (1,308.02±19.51) kg/m3, (44.13±0.49)% to (43.29±0.49)%, and (25.20±0.41)o (degrees) to (29.10±0.41)o (degrees), respectively and also increased linearly with an increase in moisture content. The average seed weight and thousand seeds weight ranged from (0.142±0.002) gm to (0.184±0.002) gm, and (177.38±2.17) gm to (194.75±2.17) gm, respectively. The average static coefficient of friction against wood, stainless steel, galvanized iron and iron surfaces and internal with the same seeds ranged from (0.430±0.016) to (0.460±0.016), (0.321±0.007) to (0.366±0.007), (0.327±0.004) to (0.371±0.004), (0.412±0.011) to (0.496±0.011) and (0.638±0.022) to (0.741±0.022), respectively. The average terminal velocity ranged from (5.18±0.34) m/s to (9.14±0.34) m/s. The average penetration depth at load 6kg and tools diameter 1 mm was determined as mechanical property, and generally increased in magnitude with an increase in moisture content. The physical properties were linearly dependent upon moisture content. Keywords: moisture, physical properties, mechanical properties, chickpea DOI: 10.3965/j.issn.1934-6344.2010.04.070-083 Citation: Ayman H. Amer Eissa, Mohamed M A, Moustafa H, Abdul Rahman O. Alghanna. Moisture dependent physical and mechanical properties of chickpea seeds. Int J Agric & Biol Eng, 2010; 3(4): 70<span style="line-height: 140%; font-family: